2016
DOI: 10.1177/1350650116632018
|View full text |Cite
|
Sign up to set email alerts
|

Friction analysis at elastic-plastic contact of rough surfaces using n-point asperity model

Abstract: The paper describes a theoretical study of friction at elastic-plastic contact of rough surfaces in n-point asperity model framework and based on accurate finite element analysis of elastic-plastic deformation of single asperity contact. Plasticity index, a well-defined nondimensional parameter is used to study the prospective situations arising out of variation in material properties and surface roughness. Using practical values of material properties and surface roughness parameters, results are obtained for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…However, in this study, because the plasticity index was 6-10, the contact state belonged to the elastic-plastic contact, and the Hertzian contact pressure and CoF were not correlated. However, Waghmare et al [26,27] reported that the elasticity index of H/E should be considered along with the Hertz contact pressure. Therefore, as shown in Figs.…”
Section: Tribological Properties Of Ta-c Coatingsmentioning
confidence: 99%
“…However, in this study, because the plasticity index was 6-10, the contact state belonged to the elastic-plastic contact, and the Hertzian contact pressure and CoF were not correlated. However, Waghmare et al [26,27] reported that the elasticity index of H/E should be considered along with the Hertz contact pressure. Therefore, as shown in Figs.…”
Section: Tribological Properties Of Ta-c Coatingsmentioning
confidence: 99%
“…With the help of a single-peak contact model of a single asperity and 3D rough surface contact model based on asperities parameters in Wen et al, 43,44 surface stress and shear stress of the workpiece surface can be obtained under a given load. Similar to the work of others, [21][22][23][24][25][26][27][28] for the convenience and efficiency of the calculation of contact model, the interaction between asperities is not taken into account.…”
Section: Contact Stress Data Acquisitionmentioning
confidence: 99%
“…To solve this problem, Wen and Tang, 17 Wei et al, 18 Wen et al, 19 and Wang et al 20 used the elastic-plastic mechanics theory to propose that in the meshing and contact analysis of rough tooth surface, the plastic hardening of asperities resulted in complicated influences of surface roughness on tooth surface contact. At the same time, some researchers put forward a series of contact models [21][22][23][24][25][26][27][28] to analyze the influence of asperities on rough surfaces. The above analysis shows that the influence of tooth surface roughness on gear contact or fatigue performance cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Same expressions are incorporated in present section to model elastic-plastic adhesive contact using n-point asperities. In earlier study also the present authors (Waghmare and Sahoo, [22]) have successfully incorporated the KE expressions for non-adhesive frictional contact. The present adhesive friction contact study is based upon RG's slip and yield theory of contacting asperities.…”
Section: Modeling Adhesive Frictional Contact: Ke Approachmentioning
confidence: 99%
“…The slipping of the asperities because of tangential load may occur either in purely elastic or elasticplastic stage-I zone of deformation. Therefore, resistance offered by such asperities before slip is calculated as frictional force using equation (19) while the resistance offered by asperities which do not slip is calculated by equation (22). …”
Section: Frictional Load Formulation For Single N-point Asperitymentioning
confidence: 99%